A time-independent reliability based design approach for rockfall net fences: a comparative analysis within the Eurocode framework. Issue 1 (August 2021) - Marchelli, Maddalena; Peila, Daniele; Biagi, Valerio De
Abstract: The design of net fences as passive mitigation measures against rockfall events has represented a challenge since the last decades. The choice of the proper effect of the actions to consider in the design is still under debate. Recently, the Authors have proposed a novel time-independent reliability approach encompassing the large variability of the size and the kinematics of the possible impacting blocks. The entire statistics of all these quantities (size, velocity, and height) enters into the calculations, differently from other approaches that consider specific values of the parameters. In addition, the variability in time of the inputs is tackled, with particular reference to the size of the falling block. The recent approach is herein merged and compared with the current semi-probabilistic ultimate limit state design approach, suggested in the Eurocodes and implemented in the Italian recommendations UNI 11211-4:2018, with the purpose of finding the equivalent partial safety factors of kinetic energy and trajectory height of the impacting block. A sensitivity analysis with different synthetic profiles, representing possible real situations, is performed highlighting that if a set of partial safety factors is assigned to different sites, an intrinsic variability in the failure probability has to be accepted.